La influencia de las canciones infantiles como técnica en el desarrollo del habla de los niños y niñas del primer año de educación básica del centro educativo de bellas artes Oswaldo Guayasamin de la ciudad de Machala en el periodo 2011 - 2012. - Díaz Suriaga, Cecilia Emérita (2015)
The development of this research work entitled The Influence of nursery rhymes AS TECHNICAL DEVELOPMENT OF SPEECH OF CHILDREN FIRST YEAR OF BASIC EDUCATION OF THE EDUCATION CENTER OF FINE ARTS Oswaldo Guayasamin, involves the application of a proactive diagnostic research work aimed at determining the influence of nursery rhymes and technical speech development in children.